2023
DOI: 10.1101/2023.03.10.531920
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparative 3D ultrastructure ofPlasmodium falciparumgametocytes

Abstract: Despite the enormous significance of malaria parasites for global health, some basic features of their ultrastructure remain obscure. In this study, we apply high-resolution volumetric electron microscopy to examine and compare the ultrastructure of Plasmodium falciparum gametocytes of both genders and in different stages of development as well as the more intensively studied asexual blood stages revisiting previously described phenomena in 3D. In doing so, we challenge the widely accepted notion of a single m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 89 publications
6
10
0
Order By: Relevance
“…While expansion microscopy is currently not feasible with MitoRed, addition of a linear epitope tag would make this marker compatible with the required denaturation step. In line with our earlier observations, we demonstrated multiple mitochondria in gametocyte stages 19 . As discussed by Evers et al, there are several possible reasons for the emergence of multiple mitochondria in gametocytes, such as adaptation to a metabolically varied environment, distribution mechanism of mtDNA, or management of reactive oxygen species.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…While expansion microscopy is currently not feasible with MitoRed, addition of a linear epitope tag would make this marker compatible with the required denaturation step. In line with our earlier observations, we demonstrated multiple mitochondria in gametocyte stages 19 . As discussed by Evers et al, there are several possible reasons for the emergence of multiple mitochondria in gametocytes, such as adaptation to a metabolically varied environment, distribution mechanism of mtDNA, or management of reactive oxygen species.…”
Section: Discussionsupporting
confidence: 93%
“…Parasites were stained for α tubulin to distinguish male and female gametocytes in stage IV and V. In stage II and III gametocytes, the mitochondrion appears as a small knot that increases slightly in size when gametocytes become more mature (Figure 2A). This is consistent with our FIB-SEM data 19 . Evers et al also showed that gametocytes have multiple mitochondria already from early gametocyte development onwards.…”
Section: Mitochondrial Dynamics During Gametocyte Development and Act...supporting
confidence: 93%
See 2 more Smart Citations
“…Clear Pf ZIP1 signals were detected at the gametocyte plasma membrane (Figure A). Male and female gametocytes were differentiated using α-tubulin as the marker. , Pf ZIP1 was at the plasma membrane, adjacent to prominent tubulin signals at the periphery of male gametocytes through stage III to V (Figure B). Pf ZIP1 was localized to the parasite plasma membrane in both male and female gametocytes.…”
Section: Resultsmentioning
confidence: 99%